2022
DOI: 10.1007/s11947-022-02828-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of High Pressure-Assisted Extraction on Yield, Antioxidant, Antimicrobial, and Anti-diabetic Properties of Chlorogenic Acid and Caffeine Extracted from Green Coffee Beans

Abstract: The bioactive ingredients of green coffee beans were extracted using high pressure-assisted extraction (HPE) and compared against those derived from the traditional heat re ux (HR) extraction method. The effect of extraction conditions on the extraction e ciency of functional components (chlorogenic acids, caffeine, total phenols, and avonoids); the free radical-scavenging activity of the extract; and the inhibition of α-glucosidase, α-amylase, and food pathogenic bacteria were measured. Using water as the sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…Hesperetin was obtained from the enzymatic hydrolysis of hesperidin and evaluated for antimicrobial activity against Gram-positive and Gram-negative bacteria, the results revealed that hesperetin more effectively inhibited the model microbes than hesperidin and hesperidin glucoside 46 . Yen et al 47 . found that chlorogenic acid was one of the main components of the water extract of green coffee beans under high pressure and demonstrated antibacterial activity against both Gram-positive ( Staphylococcus aureus and Listeria innocua ) and Gram-negative ( Escherichia coli and Salmonella enterica ).…”
Section: Resultsmentioning
confidence: 99%
“…Hesperetin was obtained from the enzymatic hydrolysis of hesperidin and evaluated for antimicrobial activity against Gram-positive and Gram-negative bacteria, the results revealed that hesperetin more effectively inhibited the model microbes than hesperidin and hesperidin glucoside 46 . Yen et al 47 . found that chlorogenic acid was one of the main components of the water extract of green coffee beans under high pressure and demonstrated antibacterial activity against both Gram-positive ( Staphylococcus aureus and Listeria innocua ) and Gram-negative ( Escherichia coli and Salmonella enterica ).…”
Section: Resultsmentioning
confidence: 99%
“…However, gastrointestinal discomfort and lactic acidosis are some adverse effects reported (Venkatakrishnan et al, 2019). Currently, there is evidence about the in vitro ability of several fruits, vegetables, and mushrooms to inhibit the activity of these human digestive enzymes (Lin et al, 2022;Papoutsis et al, 2021;Vadivel et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Various extraction techniques were employed to extract CGAs from green coffee beans including soaking (or maceration) [23][24][25]; Soxhlet extraction (or automated Soxhlet extraction) [26,27]; shaking at room temperature [6,[28][29][30][31][32], in a heated water bath [15,[33][34][35] or with cooling [36]; ultrasonic-assisted extraction [4,[37][38][39][40][41][42]; microwave-assisted extraction [43,44]; pressurized solvent extraction [45] and supercritical-fluid extraction [46].…”
Section: Introductionmentioning
confidence: 99%
“…A simple, effective and very frequently used method for cleaning up extracts of green coffee beans is by adding Carrez solutions [6,15,24,27,[29][30][31]36,47]. Other methods were also reported in the literature such as adding lead acetate solution [35,43,45] or QuEChERS extraction [38].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation